THE CORRECLATION BETWEEN STUDENTS’ LEARNING MOTIVATION AND PARENTS’ ATTENTION TOWARD THE LEARNING ACHIEVEMENT OF FUEL SYSTEM MAINTENANCE MOTORCYCLE OF TENTH GRADE STUDENTS OF SMK COKROAMINOTO WANADADI - Nugraha Priatmaja; Slamet Priyanto (Jurnal Taman Vokasi, 2014)
The objectives of this study are to descibe (1) the correlation between the students’ motiation  toward the learning achievement of fuel system maintenance motorcycle, (2) the correlation and parents’ attention toward the learning achievement of fuel system maintenance motorcycle, and (3) the correlation between students’ learning motivation and parents’ attention toward the learning achievement of fuel system maintenance motorcycle of tenth grade students of SMK Cokroaminoto Wanadadi. The study reports that (1) there was positive and significance correlation between the students’ motiation toward the learning achievement of fuel system maintenance motorcycle, (2) there was positive and significance correlation between parents’ attention toward the learning achievement of fuel system maintenance motorcycle, and (3) there was positive and significance correlation between students’ learning motivation and parents’ attention toward the learning achievement of fuel system maintenance motorcycle of tenth grade students of SMK Cokroaminoto Wanadadi. It could be interpreted that to improve students’ achievement, it was needed motivation and parents’ attention. The learning motivation was need by the students to support their learning activities because motivation was the main factor in increasing their learning achievement. The parents’ attention was also important to improve the students’ learning achievement because parents or family was the first education place for the students.